Nanometer-Thin Graphitic Carbon Buffer Layers for Electrolytic MnO2 for Thin-Film Energy Storage Devices. Issue 2 (1st January 2017) - Deheryan, Stella; Zargouni, Yafa; Sinha, Rochan; Put, Brecht; Radisic, Aleksandar; Heyns, Marc; Vereecken, Philippe M.
Abstract : In this study, nanometer thin graphitic carbon coatings were applied as an adhesion layer for the growth of submicron to micron thick electrolytic manganese dioxide (EMD) films for thin-film energy storage devices. The graphitic carbon coating served not only as current collector and adhesion layer between the EMD and the substrate, but also prevented the oxidation of the non-noble TiN substrate during the anodic deposition process. The EMD films consisted of a network of interconnected nanometer-size particles with around 50% porosity. The ability to grow a few hundred nanometer thick EMD film with good adhesion to the current collector is critical for reliable thin-film batteries on high aspect ratio microstructured surfaces. Thin EMD films grown on our graphitic carbon coated TiN substrates showed improved reversible Li-ion intercalation kinetics and increased cycle life compared to similar films deposited on noble metal platinum substrates, thus demonstrating the improved interface properties using the graphitic carbon buffer layer.